The Cambridge Handbook of Responsible Artificial Intelligence (Cambridge University Press, 2024)
There is an urgent need for responsible governance of Artificial Intelligence systems. This Handbook maps important features of responsible AI governance and demonstrates how to achieve and implement them at the regional, national and international level.